Hybrid electrons in the trimerized GaV4O8. Issue 8 (8th July 2021) - Aguilar-Maldonado, Cintli; Mentré, Olivier; Tsirlin, Alexander A.; Ritter, Clemens; Missiul, Aleksandr; Fauth, Francois; Arévalo-López, Angel M.
Abstract : Orbital–spin–charge texture in the new GaV4 O8 oxide. Abstract : Mixed-valent transition-metal compounds display complex structural, electronic and magnetic properties, which often intricately coexist. Here, we report the new ternary oxide GaV4 O8, a structural sibling of skyrmion-hosting lacunar spinels. GaV4 O8 contains a vanadium trimer and an original spin– orbital– charge texture that forms upon the structural phase transition at T S = 68 K followed by the magnetic transition at T N = 35 K. The texture arises from the coexistence of orbital molecules on the vanadium trimers and localized electrons on the remaining vanadium atoms. Such hybrid electrons create opportunities for novel types of spin, charge, and orbital order in mixed-valent transition-metal compounds.